Influence of fecal fermentation on the anthelmintic activity of proanthocyanidins and ellagitannins against human intestinal nematodes and Caenorhabditis elegans - Jato, Jonathan; Orman, Emmanuel; Boakye, Yaw Duah; Belga, François Ngnodandi; Ndjonka, Dieudonné; Oppong Bekoe, Emelia; Liebau, Eva; Spiegler, Verena; Hensel, Andreas; Agyare, Christian (Frontiers in Pharmacology, 2024)
Some tannin-rich plants such as Combretum mucronatum and Phyllanthus urinaria are widely used in Africa for the control of parasitic nematodes in both humans and livestock. Tannins have been recognized as an alternative source of anthelmintic therapies, and hence, recent studies have focused on both the hydrolyzable and condensed tannins. These groups of compounds, however, have poor oral bioavailability and are metabolized by gut microbiota into lower molecular weight compounds. The role of these metabolites in the anthelmintic activities of tannins has not been explored yet. This study investigated the effects of fecal metabolism on the anthelmintic potential of procyanidin C1 (PC1) and geraniin and the tannin-enriched extracts of C. mucronatum (CML) and P. urinaria (PUH), which contain these compounds, respectively. Metabolites were formed by anaerobic fermentation of the test compounds and extracts in a fresh human fecal suspension for 0 h, 4 h, and 24 h. Lyophilized samples were tested in vitro against hookworm larvae and whipworm (Trichuris trichiura) larvae obtained from naturally infected human populations in Pru West District, Bono East Region, Ghana, and against the wildtype strain of Caenorhabditis elegans (L4). Both extracts and compounds in the undegraded state exhibited concentration-dependent inhibition of the three nematodes. Their activity, however, significantly decreased upon fecal metabolism. Without fermentation, the proanthocyanidin-rich CML extract was lethal against hookworm L3 (LC50 = 343.5 μg/mL, 95% confidence interval (CI) = 267.5–445.4), T. trichiura L1 (LC50 = 230.1 μg/mL, CI = 198.9–271.2), and C. elegans (LC50 = 1468.1 μg/mL, CI = 990.3–1946.5). PUH, from which the ellagitannin geraniin was isolated, exhibited anthelmintic effects in the unfermented form with LC50 of 300.8 μg/mL (CI = 245.1–374.8) against hookworm L3 and LC50 of 331.6 μg/mL (CI = 290.3–382.5) against T. trichiura L1, but it showed no significant activity against C. elegans L4 larvae at the tested concentrations. Similarly, both compounds, procyanidin C1 and geraniin, lost their activity when metabolized in fecal matter. The activity of geraniin at a concentration of 170 μg/mL against C. elegans significantly declined from 30.4% ± 1.8% to 14.5% ± 1.5% when metabolized for 4 h, whereas that of PC1 decreased from 32.4% ± 2.3% to 8.9% ± 0.9% with similar treatment. There was no significant difference between the anthelmintic actions of metabolites from the structurally different tannin groups. The outcome of this study revealed that the intact bulky structure of tannins (hydrolyzable or condensed) may be required for their anthelmintic action. The fermented products from the gut may not directly contribute toward the inhibition of the larvae of soil-transmitted helminths.